Look on the bright side - Higgins, Kristan (Berkley, 2024)
"From the author of Pack Up the Moon comes a funny, romantic, and deeply moving novel about the unexpected rewards that come from life's swerves. Lark Smith was planning a fairy-tale wedding to her high school sweetheart when, in the blink of an eye, everything she dreamed of was suddenly gone. That day, Lark decided the best way to deal with loss was to prevent others from ever having to. Five years later, her goal of becoming a doctor--the best doctor--is just within reach when, without warning, she's fired. Now getting back on track means making a deal with the devil. Well, not exactly, even if they do call renowned surgeon Lorenzo Santini "Dr. Satan" behind his back. He'll use his influence to get her back in the program. But first, Lark has to pose as his significant other all summer...his sister is getting married, and he doesn't want his ninety-nine-year-old grandmother spending her precious time worrying over his single state. What Lark doesn't realize is she's already met Lorenzo's brother Dante, the firefighter who was there on Lark's worst day. The brothers couldn't be more different...which is becoming a problem, because the last thing Lark wants is to fall in love again. While spinning white lies during one unforgettable Cape Cod summer, Lark is exposed to the truth: when life throws you in the dark, love, friends, and family are there to help you look on the bright side"--